Festival hari keusahawanan 2025: where business meets buzz! - Kamal, Fatmawati; Othman, Nora Julianna; Othman, Suraya; Ab Karim, Siti Aznida; Ahmad, Fauziah; Ismail, Ilham Ameera; Abd Malek, Khasnur; Ramli Hamid, Marlina Tanty; Khalid, Zalizah; Wan Razali, Wan Mohammad Hafiz (Faculty of Medicine, 2025)
The Faculty’s annual Festival Hari Keusahawanan 2025 was anything but ordinary. It was a day when budding entrepreneurs swapped lab coats for aprons and stethoscopes for spreadsheets and turned our usually quiet faculty into a buzzing bazaar of creativity, commerce, and community!